Strategi Pemberdayaan Sumber Daya Manusia Dalam Menyikapi Transformasi Digital Di Desa Wisata - Evi Nur Sa’diyah; Raden Mas Moch Wispandono (Journal Of Business, Finance, and Economics (JBFE), 2023)
Digital transformation has become a breakthrough in targeting industrial markets, including the tourism industry in Indonesia. This is due to the people behavior who are increasingly dependent on the use of the internet in their daily activities. The current era of globalization certainly creates intense competition. An advanced nation is a nation that has qualified Human Resources (HR) and can compete globally. This research aims to describe how the strategy of empowering human resources carried out by stakehoders of Parseh Village in the tourism sector in responding to digital transformation, including the supporting and inhibiting factors felt by the Pokdarwis (a tourism awareness group). This research employed a descriptive qualitative research method with a phenomenological approach that involved the Pokdarwis Goa Poteh Jaddih as the research subject. The results of the study suggest that Pokdarwis Goa Poteh Jaddih Parseh Village is not very effective in responding to digital transformation due to the lack of awareness of the tourism employees on the importance of technology as a means of promoting and introducing tourism to the potential visitors. The strategy carried out by Pokdarwis to respond to digital transformation in tourism was increasing the knowledge and skills of Pokdarwis board members about digitalization. Pokdarwis conducted training on the basics of digital technology, such as the use of smartphones and the internet to utilize the development of Goa Poteh Jaddih tourism. Pokdarwis needs to be equipped with the skills of understanding technology to provide the best service for tourists.